2019
DOI: 10.3390/su11236715
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Habits of Local Food: Perspectives from Northern Sweden

Abstract: International studies are dealing with the promotion of sustainable food systems more frequently. Additionally, places of purchase and sharing in the choice of food to be consumed have become a network system for families. The aim of this work is to analyse the preferences of Swedish consumers for local/artisanal cheeses and the purchase motivations that guide their choices. We also studied the role played by consumers’ favourite shopping locations (retail store, hypermarket, city market, supply chain). On the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…The amount of monthly income affects their purchase strategy. Several studies have confirmed the positive effect of monthly income on domestic and regional foods [28][29][30].…”
Section: Resultsmentioning
confidence: 88%
“…The amount of monthly income affects their purchase strategy. Several studies have confirmed the positive effect of monthly income on domestic and regional foods [28][29][30].…”
Section: Resultsmentioning
confidence: 88%
“… Social, Economic, and Environment Face-to-face interviews; online survey No Local and Organic Box Schemes N = 438 Box scheme consumers N.A. H [ 122 ] Kulick, 2018 To explore how one statewide food network in the United States seeks to involve youth contending with the juvenile justice system in a job readiness program. Social Case study; participatory action research; face-to-face interview No Alternative Food Networks N = 24 Stakeholders in the local food (n = 7) and juvenile justice system (n = 17) N.A.…”
Section: Table A1mentioning
confidence: 99%
“… Social Face-to-face interviews; social network analysis No Local Food N = 200 Consumers N.A. H, R [ 122 ] Olson et al, 2019 To assesses the impact of the local food economy in Hardwick using environmental, economic, and social outcomes. Social, Economic, and Environment Face-to-face interviews No Local Food N = 21 Local Food Systems stakeholders N.A.…”
Section: Table A1mentioning
confidence: 99%
See 1 more Smart Citation
“…A significant importance is granted to the sensory impressions in the rural tourism experience [25,26], and because these are place-related [26], they are referred to as rural sensescapes. Important links exist between developing sustainable food experiences for tourists and policies for agriculture, food production [27], tourism, cultural and creative industries [28,29], especially country branding…”
Section: Rural Tourism As a Form Of Resiliencementioning
confidence: 99%